2008
DOI: 10.1177/0269216307087142
|View full text |Cite
|
Sign up to set email alerts
|

Good death study of elderly patients with terminal cancer in Taiwan

Abstract: The dilemma of truth-telling compromises the autonomy of the elderly patients with terminal cancer and consequently affects their good death scores. The palliative care team should emphasize the issue of truth-telling in the process of caring for terminally ill cancer patients, especially elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 21 publications
5
58
1
Order By: Relevance
“…In the present study, the overall proportion of unawareness of disease/prognosis is 35.1%, with 24.6% and 44.1% in the nonelderly group and elderly groups, respectively. This finding is compatible with previous research in Taiwan, which indicated that nonelderly patients had a higher level of disease awareness than elderly patients prior to death [29]. Another study from Taiwan revealed that truth‐telling problems occurred in nearly one‐half (42.6%) of the elderly population (>65 years old) with advanced cancer in Taiwan [30].…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the overall proportion of unawareness of disease/prognosis is 35.1%, with 24.6% and 44.1% in the nonelderly group and elderly groups, respectively. This finding is compatible with previous research in Taiwan, which indicated that nonelderly patients had a higher level of disease awareness than elderly patients prior to death [29]. Another study from Taiwan revealed that truth‐telling problems occurred in nearly one‐half (42.6%) of the elderly population (>65 years old) with advanced cancer in Taiwan [30].…”
Section: Discussionsupporting
confidence: 90%
“…Each item was appraised on a scale of 1 ¼ 'extremely poor' to 5 ¼ 'extremely good'. The six categories and 12 items were as follows: (1) Reliability and validity of the GDS in Taiwanese palliative care units have been well established (17,18). Cronbach's alpha (a) was used to assess the internal consistency of this good-death measure in the present study and was shown to be 0.71 for the five domains.…”
Section: The As For Good Death Servicesmentioning
confidence: 99%
“…The estimated mean and SD of the GDS were 13.77 and 2.01, respectively, based on a previous study (18). We used two-sample t-tests for comparing mean differences to calculate the required sample size.…”
Section: Sample Size Determinationmentioning
confidence: 99%
“…There is a growing body of both quantitative and qualitative research on the topic of a good death [3,4,5], including work on a Good Death Inventory [6] and a Quality of Dying and Death scale [7]. Research on quality of death has focused on the perspective of clinical caregivers [8,9], the dying person [10,11] or a combination of healthcare participants [12,13,14,15]. Although there is not full consensus in the literature about what factors or qualities contribute to a good death, there are clear overlapping aspects to a good death, including “pain and symptom management, clear decision making, preparation for death, completion, contributing to others and affirmation of the whole person” [12] (p. 825).…”
Section: Introductionmentioning
confidence: 99%